2019
DOI: 10.1017/s1355617718001169
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience as a Predictor of Symptom Severity in Adolescents With Poor Recovery Following Concussion

Abstract: Objectives: Examine the mediating effects of anxiety and depressive symptoms on the relationship between psychological resilience and post-concussive symptoms (PCS) in children with poor recovery following concussion. Participants and Methods: Adolescents (N=93), ages 13 to 18 years, were assessed at a neuropsychology screening clinic at a children’s hospital. They sustained concussions more than 1 month before the clinic visit (median time since injury=5.1 months; range=42–473 days) and were seen on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
(60 reference statements)
1
16
0
Order By: Relevance
“…These findings are in high accordance with results of previous pediatric mixed TBI-sample studies, in which it was indicated that levels of PTSS and PCS are important predictors for activities and participation [11]. A previous study emphasized that psychological resilience plays an important role in recovery from concussion in adolescents; this relationship may be negatively influenced by anxiety and depressive symptoms [22]. Therefore, emotional distress and maladaptive coping may be considered important predictors of outcome for activities and participation, as well as important components of interventions aiming to prevent longterm problems after pediatric mTBI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in high accordance with results of previous pediatric mixed TBI-sample studies, in which it was indicated that levels of PTSS and PCS are important predictors for activities and participation [11]. A previous study emphasized that psychological resilience plays an important role in recovery from concussion in adolescents; this relationship may be negatively influenced by anxiety and depressive symptoms [22]. Therefore, emotional distress and maladaptive coping may be considered important predictors of outcome for activities and participation, as well as important components of interventions aiming to prevent longterm problems after pediatric mTBI.…”
Section: Discussionsupporting
confidence: 90%
“…There are more factors which may further add to the prediction and could be investigated in future studies. For example, resilience [22] and motivation for returning to activities and participation [43,44], coping styles of children and caregivers [40], the child's self-efficacy and emotion-regulation [39], the child's and caregivers personality traits [39], the level of social support from caregivers and peers [45], and other comorbid problems, such as chronic pain, substance abuse, life stress and protracted litigation [47].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the relationship between symptom experience and psychosocial symptoms including depression have been explored. Several studies have explored the symptom experience of concussed adolescents who are slow to recover from concussion (Brooks et al, 2019; Durish et al, 2019; Stein et al, 2017). Stein et al (2017) explored symptom trajectories of depression and post‐concussive symptoms in adolescents aged 11–17 who were deemed slow to recover.…”
Section: Discussionmentioning
confidence: 99%
“…Equally important is our understanding of how mediators may alleviate troublesome symptoms like anxiety and depression during concussion recovery. Durish et al (2019) explored the mediating effect of anxiety and depressive symptoms on self‐reported psychological resilience (measured by the Connor‐Davidson Resilience Scale) and post concussive symptoms (measured by PCSI) in children who were slow to recover following concussion. The authors found that symptoms of anxiety and depression were likely mediated by psychological resilience which may impact PCS, particularly in children who are slow to recover.…”
Section: Discussionmentioning
confidence: 99%
“…Among children with delayed recovery, parent anxiety contributes additional family burden following childhood concussion, indicating a need for management strategies to consider the implications to the entire family. 86 Anxiety and depression significantly mediated the relationship between resilience and post-concussion symptoms, 108 suggesting that mental health has an important impact on recovery from concussion, even accounting for individual characteristics. While children provided different reasons for their emotional distress (eg, inability to play sport, others' lack of understanding about concussion), they consistently reported frustration, depression, anxiety, irritability and feelings of isolation associated with their injury.…”
Section: Reviewmentioning
confidence: 99%